2012
DOI: 10.2320/jinstmet.76.12
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Coercivity of Nd-Fe-B Sintered Magnets by Grain Size Reduction

Abstract: For the purpose of increasing the coercivity of the Nd Fe B sintered magnets without Dy substitution, we explored a possibility of enhancing the coercivity by grain size reduction of the sintered body by employing the starting powder with an ultimately small particle size. To produce Nd Fe B alloy powder with such a small particle size, and to handle it to produce sintered bodies without oxidation, we developed a special jet mill and a special process called pressless process (PLP). By utilizing these tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…It has also been reported that coercivity increases with decreasing grain size. 8,9 These observations and calculations suggest that the microstructure plays an important role in the determination of coercivity.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that coercivity increases with decreasing grain size. 8,9 These observations and calculations suggest that the microstructure plays an important role in the determination of coercivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the availability and price of the heavy RE elements are currently serious resource problems. Recently, the coercivity μ0Hc of Nd-Fe-B sintered magnets has been successfully enhanced to about 2 T even without addition of heavy RE elements by various methods such as refinement of the constituent crystal grains of the Nd2Fe14B phase 1) and/or grain boundary diffusion of RE elements to restore magnetic anisotropy near the grain boundaries or to suppress intergranular exchange coupling 2), 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Sagawa et al 4,5,27 applied jet mill with Helium gas as medium to bring the average particle size of Nd-Fe-B powder down to ∼1 μm. To prevent such fine particles from oxidation, they invented a so-called 'press-less pressing (PLP)' technique to compact fine powder into block in air-tight and oxygen free container.…”
Section: Introductionmentioning
confidence: 99%